Effects of personalized cosmetics on basic skin parameters monitored by non-invasive biophysical measurements - Emeti Vidović, Ana; Ivetić, Zorana; Stanivuković, Aleksandra; Terzić, Dejan (Archives of Pharmacy, 2022)
Personalized skincare approach represents actively growing area in cosmetics industry. Main advantage of personalized cosmetics is a possibility to choose ingredients according to in vivo measurements and monitoring of skin parameters. The aim of this study was to evaluate efficacy of personalized creams. Study included 90 healthy subjects, average age 35.1±12.8 years, 78 (86%) females and 12 (13.3%) males with dominantly dehydrated skin (n=54, 60%). Multi Probe Adapter (Courage & Khazaka, Germany) was used for facial skin parameters analysis: hydration, surface sebum content, erythema/melanin index and skin pH at forehead, chin and cheeks. Measurements were performed twice under controlled conditions, before and after personalized creams application. Subjects have used personalized creams twice a day during three months. Hydration was significantly increased (41.4±12.5 to 53.1±11.1; p<0.001). No significant difference is observed in melanin (148.6±37.3 to 145.5±27.8; p=0.241) while decrease is notified in erythema (361.5±80.2 to 346.9±61.3; p=0.003) and pH (5.42±0.49 to 5.32±0.39; p=0.042) which remained in optimal range. In total of 47 subjects (52%) skin hydration was significantly increased. In subjects with sebum deficiency (<70, n=66) significant increase was observed in 13 (19.7%), while at consumers with the sebum excess (>180, n=9) significant decrease was recorded in 8 (88.8%) of them. In conclusion, personalized creams application leads to significant improvement of skin hydration and sebum content normalization on cheeks alongside with erythema reduction. These results indicate efficacy of personalized skincare, and implying the possibility of following research in personal care products impact on skin behavior.